Atrial Fibrillation-Associated Ischemic Stroke Patients With Prior Anticoagulation Have Higher Risk for Recurrent Stroke. Issue 4 (April 2020) - Tanaka, Kanta; Koga, Masatoshi; Lee, Keon-Joo; Kim, Beom Joon; Park, Eun Lyeong; Lee, Juneyoung; Mizoguchi, Tadataka; Yoshimura, Sohei; Cha, Jae-Kwan; Lee, Byung-Chul; Nakahara, Jin; Suzuki, Norihiro; et al.
Abstract : Background and Purpose—: Ischemic stroke associated with nonvalvular atrial fibrillation (NVAF) despite prior anticoagulation may indicate underlying problems that nullify the stroke-preventing effects of oral anticoagulants. We aimed to evaluate the risk for recurrent stroke in patients with NVAF with prior anticoagulation, compared with that in patients without prior anticoagulation. Methods—: This study comprised pooled individual patient data on NVAF-associated acute ischemic stroke or transient ischemic attack from 2011 to 2014 arising from the Clinical Research Collaboration for Stroke in Korea (15 South Korean stroke centers) and the Stroke Acute Management With Urgent Risk-Factor Assessment and Improvement-NVAF registry (18 Japanese stroke centers). Data on 4841 eligible patients from the Clinical Research Collaboration for Stroke in Korea registry were pooled with data on all patients (n=1192) in the Stroke Acute Management with Urgent Risk-factor Assessment and Improvement-NVAF registry. The primary outcome was recurrent ischemic stroke. The secondary outcomes were hemorrhagic stroke and all-cause death. Outcome events were captured up to 1 year after the index event. Results—: Among the 6033 patients in the full cohort, 5645 patients were analyzed, of whom 1129 patients (20.0%) had received prior anticoagulation. Median age was 75 years (interquartile range, 69–81 years), and 2649 patients (46.9%) were women. Follow-up data of 4617 patient-years (median follow-up 365 days, interquartile range 335–365 days) were available. The cumulative incidence of recurrent ischemic stroke in patients with prior anticoagulation was 5.3% (60/1129), compared with the 2.9% (130/4516) incidence in patients without prior anticoagulation. The risk for recurrent ischemic stroke was higher in patients with prior anticoagulation than in those without (multivariable Cox shared-frailty model, hazard ratio 1.50 [95% CI, 1.02–2.21]). No significant differences in the risks for hemorrhagic stroke and mortality were seen between the 2 groups. Conclusions—: The risk for recurrent ischemic stroke may be higher in NVAF-associated stroke patients with prior anticoagulation than in those without prior anticoagulation. Registration—: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01581502. Abstract : Supplemental Digital Content is available in the text.